SOME SPECIES OF CALANOID COPEPODS RECENTLY DESCRIBED FROM INDONESIAN WATERS WITH NOTES ON THEIR DISTRIBUTION AND SPECIESGROUPS - Mulyadi Mulyadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
One species of the family Candaciidae, Candaciaishimarui, and four species of the family Pontellidae, Calanopiaasymmetrica, Labidocerajavaensis, L. muranoi, and Pontellalabuanensis were described from specimens collected from the Indonesian waters. C. ishimarui belong to C. norvegica group, which was hitherto composed of 3 species, C. ketchumi Grice 1961, and C. norvegica (Boeck, 1865), by having common characters of the maxilla-shape, the 3 cups of basal mandibular tooth, and the structure of P5 in both sexes. C. asymmetrica, with belong to C. herdmani group, the character of the CR and P5. L. javaensis is distinguishable from the L. pectinaya group by the shape of genital complex and he P5 in the male. It seems to be a neritic species inhabiting coastal waters shallower than 15 m in depth, and with 0.5 km off-shore. L. muranoi which was collected from Cilacap Bay. Belongs to the L. kroyeri group, and was distinguished from other species of this group by the shape of urosome and P5 in the female and by Ms5 and P5 in the male. The last described species, P. labuanensisdoes not belong to anu of the known 3 species-groups of indo-West Pacific Pontella, in having the asymmetrical genital somite and the Re’sog the P5 virtually naked in the female, and the rostrum with double convex lenses and the Re’s of the male with P5 with 2 subequal dumb.